Optimasi persentase volume total matriks alginat dan konsentrasi dekstrosa menggunakan khamir IS258 terimobilisasi untuk fermentasi bioetanol dari analog nira kelapa - Indah Sri Rejeki Naibaho; I M. Mahaputra Wijaya; I Wayan Arnata; Ida Bagus Wayan Gunam (AGROINTEK, 2025)
Cell immobilisation is a process to stop the movement of cells at a certain place in a reaction chamber that is used as a catalyst. Cell immobilisation is commonly used for various biotechnology applications, one of which is ethanol fermentation because it has the advantage of being more efficient and effective compared to using free culture. Yeast isolate IS258 is a superior isolate taken from the arak industry in Karangasem Bali which function as bioethanol fermentation agent. The immobilisation of IS258 yeast cells was made using sodium alginate which functions as an entrapment media. The calcium alginate matrix of IS258 was then used for ethanol fermentation of coconut sap analogue to replace the need of new starter. This study aimed to determine the optimal total alginate volume and dextrose concentration using immobilised IS258 yeast for bioethanol fermentation of coconut sap analogue using Response Surface Methodology (RSM). In this study, 13 variations of total volume of alginate with immobilised IS258 yeast within and dextrose concentration in coconut sap analogue media. The results showed that dextrose as a substrate was more influential than the alginate-IS258 matrix on the ethanol produced. The highest total ethanol was obtained from the treatment with matrix volume concentration of 25% (v/v) and dextrose concentration of 15% (w/v) with an average total ethanol of 93.8 ml. The D-optimally test results show that the total matrix volume concentration value has an optimal point of 19% and dextrose concentration of 24% and is expected to produce more than 80 ml of ethanol. The use of alginate-IS258 matrix has been used in ethanol fermentation for 3 times distillation for more than 25 days continuously, the results show that the ethanol produced continues to increase and the fermentation time decreases.